Ionic conductivity of oxalic acid crosslinked chitosan and application in Electrical Double Layer Capacitor (EDLC) / Iman Aris Fadzallah - Iman Aris , Fadzallah (2015)
In the present study, proton conducting solid polymer electrolytes (SPE) consisting of chitosan as polymer host, oxalic acid (OA) as proton donor and glycerol as plasticizer were prepared by solution casting method. Two systems of polymer conducting membrane composed of chitosan-oxalic acid and chitosan-oxalic acid-glycerol, namely System I and System II respectively. The ionic conductivity values for the membranes were obtained by performing electrochemical impedance spectroscopy. The membrane OA40 (containing 40 wt. % chitosan + 60 wt. % OA) in System I exhibits the highest conductivity value of 4.96 x 10-7 S cm-1. The membrane OG60 (containing 24 wt. % chitosan + 16 wt. % OA + 60 wt. % glycerol) in System II exhibits the highest conductivity value of 9.12 x 10-5 S cm-1. The ionic interaction between chitosan, OA and glycerol were studied using Fourier transform infrared (FTIR) spectroscopy. The FTIR study on System I reveals the interaction between chitosan and OA by deconvoluting the absorption peak between 1800 and 1400 cm-1. Whereas in System II, the –OH characteristic band at 3500 cm-1 become broader with the addition of glycerol which indicates the interaction between chitosan and glycerol. The amorphousness of the highest conducting membranes in both systems was confirmed by x-ray diffraction (XRD) evaluation. The crystallinity percentage was determined to be 13 and 11 % for membranes OA40 and OG60 respectively. The OG60 membrane was then fabricated into electrical double layer capacitor (EDLC) devices with symmetrical porous carbon electrodes. The electrochemical stability window was measured by linear sweep voltammetry (LSV) shows wide potential up to 2.2 V. The specific capacitance (Cs) obtained from galvanostatic charge-discharge analysis is 13 F g-1 with applied potential at 1 mA.